Material didáctico lúdico para fomentar el aprendizaje de ciencias naturales - Pintado Córdova, Joanna Mishell; Castillo Jiménez, Karen Tatiana (Machala, Universidad Técnica de Machala, 2022)
The topic that this research includes deals with the playful didactic material to promote the learning of Natural Sciences in the third-year students of the Educational Unit "Cayambe Battalion N°3" of the year 2021. With the following objectivity, generalizing the determination of the different types of playful didactic materials for the area in question where they can favor student learning; likewise, the specificities such as: identifying the use and applicability of didactic materials in the orientation of third-year students, analyzing the pros and cons of their implementation in learning, and finally establishing the use of didactic materials from the teaching part to ratify learning in the area of CC.NN. This is accompanied by the conceptual, theoretical and legal references of the subject, to corroborate and affirm the veracity with which this information is being imparted to its recipients; After that, you find the framed hypotheses that seek the management of the veracity to proceed to the following parameters such as the research approach, the level and modality of the same. The approaches are regulated from the conjunction of the qualitative and quantitative character, from an explanatory and descriptive level based on the results of the methodology and in turn manages the interpretation of the population given by the study Among the following sequences are the operations of the variables that were given by the particular hypotheses, considering the indicators that meet the requirements thereof. These were elaborated to obtain data that can be deciphered by the needs that are encompassing in educational contexts, specifically the branch of Natural Sciences to assess and improve the quality of student learning and, in turn, teacher performance. After that, the didactic guide was elaborated that shows the fundamental resolution that propitiates adjustments to the educational context, but on this occasion the beneficiaries of it would be the third-year students of the institution. After having handled the references that validate the creation of the guide and being applied by the students, the importance of gathering the need to improve the contents applied during the school year that is part of student training is concluded.
El tema que comprende esta investigación trata sobre el material didáctico lúdico para fomentar el aprendizaje de las Ciencias Naturales en los estudiantes de tercer año de la Unidad Educativa “Batallón Cayambe N°3” del año 2021. Con la siguiente objetividad, generalizando la determinación de los diferentes tipos de materiales didácticos lúdicos para el área en mención donde puedan favorecer los aprendizajes de los estudiantes; así mismo, las especificidades como: identificar el uso y aplicabilidad de los materiales didácticos en la orientación de los estudiantes de tercer año, analizar las pro y contras de la implementación de los mismos en el aprendizaje, y por último establecer el uso de materiales didácticos desde la parte docente para ratificar el aprendizaje en el área de CC.NN. Esto viene acompañado de los referentes conceptuales, teóricos y legales de la temática, para corroborar y afirmar la veracidad con la que se está impartiendo esta información hacia sus receptores; posterior a ello se encuentras las hipótesis enmarcadas que buscan los manejos de las veracidades para proceder a los siguientes parámetros como el enfoque de investigación, el nivel y modalidad de estos. Los enfoques se regulan desde la conjunción del carácter cualitativo y cuantitativo, desde un nivel explicativo y descriptivo en base a los resultados de la metodología y a su vez maneja la interpretación de la población dada por el estudio. Entre las siguientes secuencias son las operaciones de las variables que fueron dadas por las hipótesis particulares, considerando los indicadores que cumplan los requisitos de los mismos. Estos fueron elaborados para una obtención de datos que puedan descifrarse por las necesidades que van abarcando en los contextos educativos, específicamente la rama de las Ciencias Naturales para valorar y mejorar la calidad del aprendizaje estudiantil y a su vez el desempeño docente. Posterior a ello, se elaboró la guía didáctica que muestra la resolución fundamental que propicia adecuaciones al contexto educativo, pero en esta ocasión los beneficiados de la misma serían los alumnos de tercer año de la institución. Luego de haber manejado las referentes que validan la creación de la guía y ser aplicada por los estudiantes, se concluye la importancia de recabar la necesidad de mejorar los contenidos aplicados durante el año lectivo que es parte de la formación estudiantil.
Keywords: MATERIAL; ESTUDIANTE; CIENCIA NATURAL; APRENDIZAJE; METODOLOGIA; DIDACTICA